Analisis Faktor-Faktor yang Mempengaruhi Intensitas Menabung di Bank Syariah pada Masyarakat Banda Aceh - Nurfathanah, Nurfathanah (Tadabbur: Jurnal Peradaban Islam, 2020)
The growth of Islamic banking is very significant, but it is not followed by the growth of customers. The lack of customers joining Islamic banking is a problem that links to the intention of saving who visits of several factors. The aim of this study is to answer the influence of attitude factors, religiosity factors, subjective norms factor, and perceived behavioral control factors affect the intention of saving money in Islamic banks in the Banda Aceh Community, partially and simultaneously. This quantitative research, which was conducted in Banda Aceh by involving 272 samples taken using a purposive sampling technique. While the technique of collecting data was collected through questionnaires and documentation. The data analysis technique is done through SPSS statistics version 21 for windows. The results of the research indicate that: (1) Attitude factor has a positive effect on saving intention, t-count 13,200> t-table 3,327. (2). The religiosity factor has a positive effect on saving intention, t-count of 6,514> t-table 3,327. (3) The subjective factor does not affect the saving intention, t-count is 1.833 <t-table 3.327. (4) Perceived behavior control factor has an effect on saving intention, t-count is 10.324> t-table 3.327. (5) Attitude, religiosity, subjective norm, and perceived behavior control factors influence saving intention, F-count (F-statistic) 74.52> F table 1.26. (X3) the subjective norm and (X4) perceived behavior control are able to explain the variable (Y) the saving intention is 99.1%, the remaining 0.09% is explained by another variable, which is not included in this research model.